The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2010
DOI: 10.1080/03235400802075617
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Kocide and Ridomil plus fungicides on the mycoflora of tomato plant in Upper Egypt

Abstract: Kocide 101 (77% cupric hydroxide) and Ridomil plus (15% metalaxyl and 35% copper oxychloride) were used in the treatment of tomato plants in the field. Generally, the two fungicides exhibited an inhibitive effect on the total and individual counts of glucophilic fungi after different periods of treatment except in some cases, the counts were not affected or promoted compared with the control. Fungal genera and species associated with roots and shoots of tomato plants were isolated from untreated plants as cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
1
0
0
Order By: Relevance
“…Seedling fresh weight determinations :both of ethyl benzoate (5ppm) and sorbic acid (10ppm) realized similar effects as ridomil MZ (1.5x) on seedling fresh weight. Our findings were in agreement with those of Magarey and Bull (1994) and Saleem, (2010), who reported that mancozeb augmented shoot and root dry weight of sugarcane. Furthermore, Magarey and Croft (1995) reported that metalaxyl reduced shoot and root dry weight.…”
Section: Effects Of the Tested Treatments On Certain Plant Growth Parameterssupporting
confidence: 94%
“…Seedling fresh weight determinations :both of ethyl benzoate (5ppm) and sorbic acid (10ppm) realized similar effects as ridomil MZ (1.5x) on seedling fresh weight. Our findings were in agreement with those of Magarey and Bull (1994) and Saleem, (2010), who reported that mancozeb augmented shoot and root dry weight of sugarcane. Furthermore, Magarey and Croft (1995) reported that metalaxyl reduced shoot and root dry weight.…”
Section: Effects Of the Tested Treatments On Certain Plant Growth Parameterssupporting
confidence: 94%